Architecture on Common Ground. The Question of Land: Positions and Models. - (:unkn) unknown (Lars Müller, 2020)
How we deal with land has far-reaching implications for architecture and urban development. The last decade has seen a dramatic rise in the privatization of urban land and in speculation. Many European cities that today find themselves under extreme development pressure have virtually no land left to build on. In view of the acute housing shortage, the issue of who owns the land is therefore more relevant than ever: To what extent are we able to treat the land as a common good and guard it from the excesses of capitalism? After a number of specialist journals have already addressed the land property issue, this book aims to dig deeper by providing a historical overview spanning an arc from Henry George to the present day. Interviews with stakeholders in global models provide insights into the current handling of the issue. The book presents outstanding projects based on either a legal or spatial distribution of land and thus makes a valuable contribution to the current discussion on sustainable land policy.
Keywords: Bodeneigentum; Urbaner Raum; Grundeigentum; Bodennutzung; Knappheit; Ideengeschichte; Bodenreform; Bodenpolitik; Bodenrecht; Erbpacht; Liegenschaftspolitik; Enteignung; Sozialer Wohnungsbau; Wohnungsfrage; Projektauswahl; Bodenfrage; Commons